Correlation between FTIR fingerprint spectra and inhibition of α-glucosidase activity of Andrographis paniculata using partial least squares regression analysis - Rafi, Mohamad; Stevanus, Stevanus; Aziz, Zuhelmi; Anggela, Retti Hanggia; Saputra, Agus (Chimica et Natura Acta, 2026)
Andrographis paniculata has been used empirically by people as traditional medicine to treat diabetes. In this study, we correlated the FTIR spectra and α-glucosidase inhibition by using chemometrics analysis to obtain a functional group from the metabolite present in A. paniculata herb exhibited α-glucosidase inhibitory activity. A. paniculata herb powder was extracted using water, ethanol, ethyl acetate, and n-hexane using ultrasonication method. The dried extract obtained was then measured for its FTIR spectra and determined for α-glucosidase inhibitory activity. Absorbance data from the FTIR spectra of A. paniculata herb extracts were used as a principal component analysis (PCA) variable for grouping extract based on the solvent extractor used. In addition, partial least square regression analysis (PLSR) is also used to predict functional groups from metabolites that cause inhibition of α-glucosidase. In the PLSR, we correlated using the FTIR spectrum's absorbance values and IC50 of α-glucosidase inhibitory activity. Before being subjected to PCA and PLSR, the FTIR spectrum was preprocessed using standard normal variate. PCA using the absorbance data from 1800–1000 cm-1 and 2800–3400 cm-1 could group the extract based on extracting solvent used with a cumulative percentage of the two principal components (PC), namely PC-1 and PC-2 are 86%. The PLSR analysis showed that OH, C=O, C=C, and C-O are the predicted functional groups related to the inhibition of α-glucosidase. So, those functional groups are present in the metabolites in A. paniculata herb extracts that contributed to the inhibition of α-glucosidase.